THE SIGNIFICANCE OF FAST DIAGNOSTICS OF SARS-COV-2, GOOD HEALTH CARE ORGANIZATION AND REASONABLE USE OF KNOWLEDGE AND RESOURCES IN THE FIGHT AGAINST COVID-19 - Arsic Arsenijevic, Valentina; Skvarc, Miha (HEALTH CARE, 2020)
In December 2019, a new disease appeared, that is, pneumonia of unknown cause, which was linkedto a seafood market in Wuhan (China). Human respiratory epithelial cells were used to isolate a novelcoronavirus, named according to the clinical picture “Severe Acute Respiratory Syndrome Coronavirus 2”(SARS-CoV-2), whereas the disease was named the coronavirus disease 2019 (Covid-19). This pandemichas proved to be a great challenge for all professionals dealing with microbiological diagnostics, as wellas for all health care workers. The aim of this work is to present the significance of fast diagnostics ofSARS-CoV-2, the significance of protection of health of health care workers, and the reasonable useof knowledge and resources in the fight against Covid-19. The previous research has confirmed thatin the fight against the SARS-Cov-2 infection, fast diagnostics of SARS-CoV-2, protection of health ofhealth care workers and reasonable use of knowledge and resources during the pandemic are of utmostimportance. A special emphasis is put on the vaccination against seasonal influenza, as well as againstthe invasive pneumococcal disease because, with the help of these vaccines, the diagnosis of Covid-19could be made easier in the future period, in which the efficient antiviral therapy for SARS-CoV-2 andthe vaccine for Covid-19 are expected with great hopes.
Keywords: Covid-19, SARS-CoV-2, microbiological diagnostics, health care workers, knowledge, resources